(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This study was carried out primarily to investigate the relationship between guest accommodation attributes and guest retention in the hospitality industry in Port Harcourt, Rivers State, Nigeria. The objectives of the study were to; determine the influence of three hotel attributes (hospitality, ambience and hotel security) on retention of hotel guests. Descriptive survey research design was adopted for the study. The population of study was large and unknown. Consequently, the sample size of 246 determined using Freund and Williams formula for sample size determination from a infinite population. Primary data were collected a well structured questionnaire and administered to the guests of hotel organizations in Port Harcourt, Rivers State, Nigeria. Major findings show that the three dimensions of guest accommodation attributes had positive significant relationship with guest retention. It was recommended that, The owners/managers of hotels should take cognizance of the strategic importance of all the accommodation attributes capable of influencing guests’ brand preferences. To achieve this objective, the marketing strategy towards enhancing hospitality in the hotels could involve promoting the local dishes of the community where the hotel is located, enhance the level of entertainment, improve the ambience or servicescape. Also, appropriate security measures should be taken to ensure that the hotel environment is properly secured